Integrasi Edukasi Gizi, Praktik Pangan Bergizi, dan Prenatal Yoga dalam Pencegahan Stunting di Desa Legok Kaler: Pengabdian - Jihan Nazhifa Khoer; Nurlaela Hamidah; Selvia Nur Haliza; Muhammad Al Gifari Ramadhan; Rissa Khalida Yusup; Mia Lukluul Milah; Cica Cahyati; Muhammad Husaini Nurul Hakim; Muhammad Linggar Antara; Rifa Hasna Hanifah; Silmy Halwany Ajda Haifa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Stunting is one of the chronic nutrition problems in Indonesia that impacts the quality of child development and can reduce the nation's competitiveness in the long run, thus requiring comprehensive and sustainable preventive efforts. This community service activity is organised with the aim of increasing knowledge and raising awareness among residents regarding the importance of stunting prevention through balanced nutrition education and strengthening the health of pregnant women. This programme is conducted in Legok Klaer Village, Cicaruy Hamlet, Sumedang Regency, involving 34 mothers with toddlers. The methods used include the distribution of materials using posters and brochures, interactive discussions, anthropometric examinations, and assistance in preparing balanced nutrition menus. The series of activities is reinforced through the implementation of Healthy Kitchens to Address Stunting (DASHAT), Stunting Consultative Forums, and Prenatal Yoga Practices aimed at improving the physical and psychological health of pregnant women. The results indicate an improvement in participants' understanding, as seen from their ability to answer questions more accurately and provide examples of balanced nutrition application in daily life. Furthermore, Prenatal Yoga attended by pregnant women has proven beneficial for psychological calmness and physical fitness. The success of this program is closely linked to the active involvement of the community, the role of posyandu cadres, and the support of the village government. Therefore, the combination of nutrition education, nutritious food practices, and strengthening the health of pregnant women through the prenatal yoga program can be considered an effective comprehensive strategy in efforts to reduce stunting rates at the village level.